Influence of geometric shape on the deformation performance of natural jute/epoxy specimens under axial quasi-static compression - Hamza, Sabah Salim; Yaakob, Mohd. Yuhazri; Ismail, Al Emran; Al Absi, Salih Meri (The Mattingley Publishing Co., Inc., 2019)
The interest in the using of natural composite has been increased significantly in recent years in many application of life due to their distinctive characteristics these like low density, high-energy dissipation ability, and fatigue resistance. Indeed, a seemingly good alternative candidate to metals.This work displays the deformation performance of two different types of geometrical natural composite shapes when subjected to uniaxial quasi-static loading. The purpose is to study the effect of geometrical on the progressive collapse of composite specimens. Two geometrical composite tubes have been fabricated by combination technique of manual lay-up and vacuum bladder moulding. The two types of the proposed tubes, which are the circular and corrugated shape. The experimental work was performed by using bidirectional jute fabric (with 3 layers and 100mm in length) and epoxy resin. Six patterns (three for each one) were tested and evaluated in the same conditions to provide a proper means of comparison between different geometric shapes. The result exhibited both kinds of samples demonstrated stable and progressive deformation with acceptable repeatability during the test process. It also showed the ability to absorb the higher energy of the corrugated samples configuration than the circular samples. Overall, the corrugated pattern configuration can be considered the optimal for crashworthiness structure application compared to a circular composite sample.